Hydrology and geomorphology of select Great Plains rivers - Costigan, Katie Helen (Kansas State University, 2013)
Great Plains rivers are unique systems that vary from large, continental scale, to small intermittent streams with grain sizes that range from bedrock to cobbles to silt. These rivers have been subject to widespread hydrologic alteration both within the channel and the watershed, which has resulted in an alteration in their hydrologic and geomorphic regimes. Although there is an acknowledgement of this alteration, to date there has not been a synthesis of the hydrology of Great Plains rivers or of their longitudinal morphologies. Chapters in this dissertation provide, to my knowledge, the first comprehensive analyses of the hydrology and morphology of Great Plains rivers over a range of spatial and temporal scales. In the first study, I found that there was no uniform pattern of hydrologic alteration throughout the Great Plains, which is likely attributable to variable system-specific reservoir management objectives, land use changes, and climatic regimes over the large area the Great Plains encompass. Results of this study are the first to quantify the widespread hydrologic alteration of Great Plains rivers following impoundment. In the second study, I found an apparent decoupling between local moisture conditions and streamflow in intermittent prairie streams. Results of this study used statistical models to identify relationships between flow intermittence, mean annual flow, and flood flow characteristics with moisture to characterize flow in an intermittent prairie stream. In the final study, I found that the downstream trends in hydraulic geometry and substrate characteristics of the Ninnescah River were consistent with the expected trends proposed by hydraulic geometry and substrate theories. However, there were points that deviated from the expected trends, most notably where a substantially large tributary enters the Ninnescah River and as the Ninnescah River approaches the Arkansas River, and causal explanations for these deviations were explored. Results of this study are, to my knowledge, the first of its kind to assess the longitudinal hydraulic geometry and substrate characteristics of a large sand-bed river over a large spatial scale. To our knowledge, there have been no comparable studies exist that attempted to describe hydrologic and geomorphic characteristics of prairie streams.
Keywords: Hydrologic sciences; Geomorphology; Geomorphology (0484); Hydrologic Sciences (0388)